Analysis of some decisions of the Plenum of the Constitutional Court of the Republic of Azerbaijan regarding real estate - Dadashov, Emin Teyyub (Теоретичні питання юриспруденції і проблеми правозастосування: виклики ХХІ століття : тези доп. учасників X Міжнар. наук.-практ. конф. (Харків, 25 трав. 2025 р.), 2025)
The legal positions of the Plenum of the Constitutional Court of the Republic of Azerbaijan on issues related to real estate have direct legal force and are mandatory for everyone in the territory of the Republic of Azerbaijan as a result of the interpretation of the Constitutional norms, civil law norms, as well as other legal norms. While formulating its legal positions on issues related to real estate, the Plenum of the Constitutional Court referred to domestic legal norms and decisions of the European Court of Human Rights, as well as decisions of the Constitutional Courts of some foreign countries.